IMPLEMENTASI TEKNIK PENGAMBILAN GAMBAR OLEH DIREKTUR FOTOGRAFI DALAM PRODUKSI VIDEO FEATURE "QUIET QUITTING: THE BALANCE WITHIN" - Ulhaq, Daffa Dhiya; Zubair, Feliza; Dewi Risanti, Yuliani (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study examines the implementation of cinematographic techniques by the Director of Photography (DOP) in the feature video Quiet Quitting: The Balance Within. The video explores the quiet quitting phenomenon, where individuals choose to work only within their assigned responsibilities without exceeding expectations, aiming to maintain work-life balance. The objective of this study is to analyze how visual storytelling techniques—such as type shots, camera angles, camera movement, and framing—contribute to conveying the themes of quiet quitting. This research adopts a qualitative descriptive approach using case study analysis. The study focuses on visual techniques applied throughout the pre-production, production, and post-production phases. Data collection methods include direct observation, video analysis, and interviews with key production members. The cinematographic aspects analyzed include close-up shots to emphasize emotions, medium shots to establish context, high and low camera angles to shape perspective, tracking and static shots to regulate the pacing, and framing techniques to highlight solitude, disconnection, and emotional engagement. The results indicate that the integration of cinematographic elements significantly enhances audience perception and emotional connection. The selection of shot types effectively conveys the psychological and emotional depth of the protagonist, while camera angles and movements reinforce themes of isolation and workplace detachment. This study contributes to media studies by demonstrating how cinematographic techniques can visually translate abstract workplace experiences into compelling narratives.